Physico-chemical properties and shelf life of sausage available in local markets in Bangladesh - Hossain, MT; Badhan, SJ; Juthi, JF; Mahbub, MM; Hasan, MR; Nahar, S; Murshed, HM; Azad, MAK (Meat Research, 2025)
The increasing demand for chicken sausages has made them very popular. The goal of this study was to look at and compare the quality of four brands of sausage that are sold in stores in Mymensingh, Bangladesh. A thorough set of analysis was done, including sensory evaluation (color, flavor, juiciness, and overall acceptability), proximate composition analysis (moisture, crude protein, ether extract, and ash), and physicochemical characteristics (pH, water-holding capacity, drip loss, cooking loss, water activity, shear force, and instrumental color measurements). The results showed that the four sausage brands were very different in terms of quality. Brand A generally had a better taste and was more acceptable overall. It also had the lowest cooking loss and shear force, which means it was more tender and appealing to customers. On the other hand, Brand C had a lower pH and water holding capacity, which could affect texture and preservation. The proximate composition analysis showed that the protein content was moderate (about 10–18%) and the fat content varied, which could affect the health of consumers. Physicochemical analysis revealed substantial variations in moisture retention and texture, indicative of differences in formulation and processing techniques. In conclusion, the study shows that sausages sold in local markets meet most people's needs, but there are big differences in how they taste and how healthy they are. These results can help both consumers make healthier choices and manufacturers come up with better ways to make their products, which will improve quality and fit with modern health-conscious tastes. The study underscores the necessity for quality control protocols and regulatory supervision to maintain uniform standards in Bangladesh's expanding processed meat sector.